Circulation of Drugs Without a Permit Seen from the Side of Law Enforcement - David Lintangadi; Nuvazria Achir (Estudiante Law Journal, 2022)
This study aims to determine the circulation of drugs without a permit seen from the side of law enforcement. The method used in this research is the research methodology used is empirical research and uses a qualitative descriptive approach and qualitative analysis techniques. The results of this study indicate that law enforcement carried out by the Food and Drug Supervisory Agency includes two things, namely law enforcement before a case occurs and law enforcement after a case occurs. Law enforcement before a case occurs is usually carried out to provide socialization in the community and schools regarding awareness of the legal dangers of drug distribution without BPOM permission. While law enforcement after a case has occurred, the authorities usually take repressive action where the action takes the form of a legal process by applicable regulations.